Loeys-Dietz syndrome as a cause of aortic dissection type A. - Jany Rodríguez Londres; Roger Ravelo Dopico; Gretell Medina Guirola; Lisbeth González González; Ailema Alemán Fernández (ECIMED, 2011)
Loeys-Dietz syndrome is considered a genetic disorder with autosomic dominant transmission and defined by a characteristic triad: generalized arterialtortuosity and aneurysms, hypertelorism and cleft palate or split uvula. The arterial affection, especially aortic dissection and dilatation, is the main cause ofdeath in those patients. It is presented a clinic case with mentioned characteristics, being carried out the diagnosis of this entity so not very frequent andinteresting, like cause of dissection aortic type A.